Grands et Jeunes d'Aujourd'hui : XIIe Salon. - XIIe Salon : Grands et Jeunes d'Aujourd'hui, Paris, 1971 (Paris : Pavillon Baltard 11, 1971)
Agam ; Bon, Liliane ; Armando, Perz ; Boto, Martha ; Careaga, Enrique ; Calos, Nino ; Cavell, Marc ; Colmenarez, Asdrubal ; Cruz-Diez ; Demarco, Hugo ; Erb, Léo ; Hanich, Davos ; Lucena, Victor ; Merida, Manuel ; Marquez, Ruben ; Ojeda, Esther ; Perez, Rafael ; etc.
XIIe Salon : Grands et Jeunes d'Aujourd'hui, Pavillon Baltard 11, Paris, 26 mars au 26 avril 1971
boek